The relationship between psychosocial work factors, employee health and organisational production: A systematic review - Malin Lohela Karlsson; Christina Björklund; Irene Jensen (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
The aim of this systematic review is to establish the research evidence of the relationship between the psychosocial work environment and employee health and its impact on organisational production. Searches in several databases were performed in September 2009. Previously known studies were also included. A total of 17 studies were identified using these methods. Study quality was evaluated using the EPHPP quality assessment tool. We found limited evidence that psychosocial work factors and employee health are predictors of production loss. The evidence was clearest with regard to job strain and musculoskeletal pain. Although there was some evidence for the impact of psychosocial work factors and the health of employees on self-rated performance, there was no evidence for any specific factors or health problems. The research into how psychosocial work factors and employee health affect organisational production still suffers from the fact that there are only few and low-quality studies. Longitudinal studies that evaluate the factors that create healthy organisations are needed.
Keywords: I12; I15; J28; J81; L25; M12; 330; Evidence-based; organisational production; psychological factors; working conditions; healthy organisations; healthy workplaces; Arbeitsgestaltung; Arbeitsbedingungen; Betriebliches Gesundheitsmanagement; Gesundheit; Unternehmenserfolg